The influence of banner advertisements on attention and memory: human faces with averted gaze can enhance advertising effectiveness - Sajjacholapunt, Pitch; Ball, Linden J. (Frontiers in Psychology, 2014)
Research suggests that banner advertisements used in online marketing are often overlooked, especially when positioned horizontally on webpages. Such inattention invariably gives rise to an inability to remember advertising brands and messages, undermining the effectiveness of this marketing method. Recent interest has focused on whether human faces within banner advertisements can increase attention to the information they contain, since the gaze cues conveyed by faces can influence where observers look. We report an experiment that investigated the efficacy of faces located in banner advertisements to enhance the attentional processing and memorability of banner contents. We tracked participants’ eye movements when they examined webpages containing either bottom-right vertical banners or bottom-centre horizontal banners. We also manipulated facial information such that banners either contained no face, a face with mutual gaze or a face with averted gaze. We additionally assessed people’s memories for brands and advertising messages. Results indicated that relative to other conditions, the condition involving faces with averted gaze increased attention to the banner overall, as well as to the advertising text and product. Memorability of the brand and advertising message was also enhanced. Conversely, in the condition involving faces with mutual gaze, the focus of attention was localised more on the face region rather than on the text or product, weakening any memory benefits for the brand and advertising message. This detrimental impact of mutual gaze on attention to advertised products was especially marked for vertical banners. These results demonstrate that the inclusion of human faces with averted gaze in banner advertisements provides a promising means for marketers to increase the attention paid to such adverts, thereby enhancing memory for advertising information.